Tradisi Ontalan di Madura: Perspektif Hukum Syafi’i dalam Pernikahan Islam - Subadar Alwy (Prodi Ahwal Al-Syakhsiyyah STAI Imam Syafi'i Cianjur, 2024)
Ontalan is a tradition deeply rooted in Madurese culture and is carried out in the context of wedding celebrations. The term